European Inventory on Validation: 2014 Update - Cedefop (2014)
The 2014 inventory update, compiled in cooperation with the European Commission, closely reflects the European guidelines on validation. It includes 36 reports for 33 countries, eight in-depth thematic reports, two case studies and a synthesis report of main findings. The reports present information up to January 2014.
Keywords: formation des adultes